Impact of serotonin transporter gene on rTMS augmentation of SSRIs for obsessive compulsive disorder - Zhang K (Dove Medical Press, 2019)
Kai Zhang,1,2,* Xiwang Fan, 1,* Jianmin Yuan,1 Jiajun Yin,1 Hang Su,3 Kenji Hashimoto,2 Guoqiang Wang11Wuxi Mental Health Center, Nanjing Medical University, Wuxi, People’s Republic of China; 2Division of Clinical Neuroscience, Chiba University Center for Forensic Mental Health, Chiba, Japan; 3Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workObjective: Repetitive transcranial magnetic stimulation (rTMS) is beneficial for treatment-resistant patients with obsessive-compulsive disorder (OCD). The serotonin transporter gene (SLC6A4) may be associated with OCD. We aimed to determine whether SLC6A4 impacts the beneficial effects of rTMS in patients with OCD treated with selective serotonin reuptake inhibitors (SSRIs).Methods: Fifty-seven untreated patients with OCD were randomly assigned to receive active or sham rTMS in a 4-week double-blind study. The participants received 1-Hz rTMS over the supplementary motor area once per day, for 5 days a week, for 4 weeks. One of the widely employed SSRIs was utilized at the initiation of active or sham rTMS. Yale–Brown obsessive–compulsive scale (Y-BOCS) scores were used for assessing the symptoms. The most-researched polymorphism of SLC6A4, 5-HTTLPR (L/S), was also examined.Results: Y-BOCS scores in the active group at the completion of the treatment were significantly lower than those in the sham group. Interestingly, the improvement in Y-BOCS scores in patients with the LL genotype treated with active rTMS was significantly (p<0.05) greater than in those treated with sham rTMS. Conversely, rTMS did not produce significant improvements in S allele carriers.Conclusions: The findings of this study suggest that rTMS can augment the beneficial effects of SSRIs in OCD patients with the LL genotype of 5-HTTLPR. Therefore, the presence of 5-HTTLPR (L/S) in SLC6A4 may be a predictable biomarker for the beneficial effects of rTMS, although more studies using larger sample sizes are warranted for confirming the results.Keywords: obsessive-compulsive disorder, repetitive transcranial magnetic stimulation, 5-HTTLPR, polymorphism